2010
DOI: 10.1124/jpet.110.167643
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Propranolol on Bone Metabolism in Spontaneously Hypertensive Rats

Abstract: The effects of propranolol (PRO), a nonselective ␤-adrenergic receptor (␤-AR) antagonist with membrane-stabilizing action on bone metabolism, were examined in spontaneously hypertensive rats (SHR) showing osteoporosis with hyperactivity of the sympathetic nervous system. Treatment of SHR with PRO at 1 and 5 mg/kg p.o. for 12 weeks increased bone mass of the lumbar vertebra and proximal tibia without affecting blood pressure, but PRO at 50 and 100 mg/kg with hypotensive action did not increase bone mass. Next, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 35 publications
4
35
0
1
Order By: Relevance
“…The effect of the lowest dose was consistent with the early observation of Minkowitz et al [24] and subsequent studies of Bonnet et al [3,4]. There was an attenuated antiosteoporotic effect of propranolol at 10 mg/kg/day po compared to 0.1 and 1 mg/kg/day po in spontaneously hypertensive rats; however, no deleterious effect of propranolol at 50 and 100 mg/kg/day po on the trabecular microarchitecture of bones was reported [31]. Positive effects of propranolol were reported after its use in drinking water (500 mg/l) in rats with bone changes induced by mechanical unloading [22] and in other rat studies [1,42].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The effect of the lowest dose was consistent with the early observation of Minkowitz et al [24] and subsequent studies of Bonnet et al [3,4]. There was an attenuated antiosteoporotic effect of propranolol at 10 mg/kg/day po compared to 0.1 and 1 mg/kg/day po in spontaneously hypertensive rats; however, no deleterious effect of propranolol at 50 and 100 mg/kg/day po on the trabecular microarchitecture of bones was reported [31]. Positive effects of propranolol were reported after its use in drinking water (500 mg/l) in rats with bone changes induced by mechanical unloading [22] and in other rat studies [1,42].…”
Section: Discussionsupporting
confidence: 86%
“…It was demonstrated that activation of b -adrenergic receptors in osteoblasts and stromal cells leads to the inhibition of bone formation and intensification of bone resorption [36,37]. Propranolol, a nonselective b-receptor antagonist, was reported to be effective in counteracting bone damage in different experimental models of bone disorders [1,6,22,31,34,35,42]. Results of some, but not all, human studies [5, 12, 23, 27-30, 32, 41] confirm the hypothesis that b-blockers may decrease the fracture rate.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have demonstrated that the sympathetic nervous system is involved in bone metabolism (Cherruau et al, 1999;Elefteriou et al, 2005;Togari and Arai, 2008;He et al, 2011). Bone loss can be induced by continuously high sympathetic tone and this is reversed by b-adrenoceptor blockade (Bonnet et al, 2008;Sato et al, 2010). Previous studies, including ours, showed that mRNAs of both a-and b-adrenoceptors were expressed in human osteoblasts (Togari et al, 1997;Togari, 2002;Huang et al, 2009).…”
Section: Introductionmentioning
confidence: 69%
“…Both experimental and clinical studies have demonstrated that b-adrenoceptor blockade is effective against osteoporosis accompanied by a highly active sympathetic nervous system (Pasco et al, 2004;Bonnet et al, 2007;Sato et al, 2010;Yang et al, 2011). There is also a report that a1-adrenoceptor blockade increased the risk of hip/ femur fracture (Souverein et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation